Investigating the effectiveness of point features matching for detecting gun items - Nur Najwa, Ibrahim (2018)
Every entry point has national high-security to ensure no firearms brought illegally. This is a crime if carry firearms without consent from authorities. However, even though many ways have been implemented to detect gun items from entering the county, such as Point Features Matching (PFM) the gun still manage to pass through safety security checks. The objective of this study is to detect gun items using Point Features Matching (PFM) and to investigate the effectiveness of Point Features Matching (PFM) with respect to the size and position of scene images. Point Features Matching (PFM) is to identify or detect a particular object in cluttered scene and given a reference image of the object. Particularly in this study, gun are the items that will be detected using Point Features Matching (PFM). Based on the experiments conducted, the PFM is effectively detect the gun items regardless the different position and various size when the percentage similarity of matching points more than or equal 50%.